ACCELERATED GROWTH IN EARLY CHILDHOOD IS ASSOCIATED WITH INCREASED SYSTOLIC AND DIASTOLIC BLOOD PRESSURE. (18th May 2018) - Eny, Karen; Maguire, Jonathon; Dai, David; Lebovic, Gerald; Adeli, Khosrow; Hamilton, Jill; Hanley, Anthony; Mamdani, Muhammad; McCrindle, Brian; Tremblay, Mark; Parkin, Patricia; Birken, Catherine
Abstract: BACKGROUND: Maternal obesity, low birthweight, and accelerated growth have been shown to be associated with elevated blood pressure in children. However, it is unknown which growth periods are associated with blood pressure, and whether birthweight or maternal obesity modify the relationship between growth and blood pressure in early childhood. OBJECTIVES: We examined the relationship between age- and sex-standardized body mass index (zBMI) growth trajectories with longitudinal measures of systolic (SBP) and diastolic (DBP) blood pressure in early childhood. DESIGN/METHODS: We collected repeated measures of zBMI and blood pressure in 2502 children participating in the TARGet Kids! cohort. In stage 1 we used linear spline multilevel models to estimate each child's zBMI at birth and zBMI growth trajectories in early infancy (0–3 m), late infancy (3–18 m) and toddler years (18–36 m). In stage 2 we used generalized estimating equations to examine the relationship between zBMI at birth and zBMI growth with repeated measures of SBP and DBP from 3 to 6 years of age. We tested for effect modification by birthweight and maternal obesity status by inclusion of interaction terms in each growth period. RESULTS: After adjusting for confounders and prior growth, a 1 standard deviation unit increase in zBMI growth per month in early infancy (β=0.59; 95% CI 0.32, 0.87) and late infancy (β=0.73; 95% CI 0.44, 1.01), were associated with higher SBP. Growth in the toddler years was not significantly associated with SBP (p=0.08). Similar but smaller associations were observed for zBMI growth and DBP in early (β=0.29; 95% CI 0.04, 0.53) and late infancy (β=0.42; 95% CI 0.18, 0.66). Birthweight status modified (p=0.004) the relationship between zBMI growth and SBP during late infancy, with the strongest positive association observed in the low birthweight group. During toddler years, birthweight status modified the relationship between zBMI growth with SBP (p=0.03) and DBP (p=0.04), with the strongest positive association observed in the low birthweight group, followed by the high birthweight group. Maternal obesity status modified (p= 0.03) the relationship between zBMI growth with DBP in late infancy, with a stronger association observed among children of mothers with obesity. CONCLUSION: Accelerated growth in early and late infancy are associated with increased blood pressure in early childhood. Growth during late infancy and toddler years may impact blood pressure differently in children born with high and low birthweights and high maternal BMI, suggesting prospective windows and risk groups to target interventions.